2010
DOI: 10.1164/rccm.200907-0989oc
|View full text |Cite
|
Sign up to set email alerts
|

HIV Coinfection in Multidrug- and Extensively Drug-Resistant Tuberculosis Results in High Early Mortality

Abstract: Mortality from MDR and XDR TB in this high HIV-prevalence region is extraordinarily high, particularly within the first 30 days. Efforts to reduce mortality must focus on earlier diagnosis and early initiation of second-line TB and antiretroviral therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
237
4
7

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 269 publications
(263 citation statements)
references
References 25 publications
13
237
4
7
Order By: Relevance
“…2) (111,263). The higher case-fatality rate of TB in HIV-infected individuals is likely due to a combination of factors associated with HIV coinfection: (i) the rapid progression of disease due to the failure of immune responses to restrict the growth of Mycobacterium tuberculosis, (ii) delayed diagnosis and treatment of TB infection due to atypical presentation and lower rates of sputum smear positivity (33,53,122), (iii) delayed diagnosis of HIV infection due to stigma or insufficient uptake of HIV testing in TB clinics (122,262), (iv) delayed start or lack of access to combination antiretroviral therapy (ART) (122), and (v) higher rates of multidrug-resistant (MDR) TB (MDR-TB) leading to a delayed initiation of effective therapy (104). Deaths due to TB accounted for one-quarter of the estimated 2 million HIV-related deaths worldwide in 2008, and TB is the leading cause of death for people living with HIV in low-and middle-income countries (155,250,262,263).…”
Section: Scale Of the Problem: Millions Affected And Millions Of Livementioning
confidence: 99%
See 2 more Smart Citations
“…2) (111,263). The higher case-fatality rate of TB in HIV-infected individuals is likely due to a combination of factors associated with HIV coinfection: (i) the rapid progression of disease due to the failure of immune responses to restrict the growth of Mycobacterium tuberculosis, (ii) delayed diagnosis and treatment of TB infection due to atypical presentation and lower rates of sputum smear positivity (33,53,122), (iii) delayed diagnosis of HIV infection due to stigma or insufficient uptake of HIV testing in TB clinics (122,262), (iv) delayed start or lack of access to combination antiretroviral therapy (ART) (122), and (v) higher rates of multidrug-resistant (MDR) TB (MDR-TB) leading to a delayed initiation of effective therapy (104). Deaths due to TB accounted for one-quarter of the estimated 2 million HIV-related deaths worldwide in 2008, and TB is the leading cause of death for people living with HIV in low-and middle-income countries (155,250,262,263).…”
Section: Scale Of the Problem: Millions Affected And Millions Of Livementioning
confidence: 99%
“…Gandhi et al investigated the prevalence rates of MDR-TB and XDR-TB in a region with HIV prevalence rates of 20% in maternity wards and 37% among women receiving antenatal care (103,104). Of the 1,539 patients tested, 542 (35%) had culture-positive TB, with MDR-TB in 221 (41%) of those with culture-positive TB.…”
Section: Drug-resistant Tuberculosis and Hiv: A Deadly Syndemicmentioning
confidence: 99%
See 1 more Smart Citation
“…При сравнении пациентов с ШЛУ и МЛУ оказалось, что единственным существенным фактором риска ШЛУ туберкулеза является ВИЧ инфекция [24]. [26].…”
Section: обзорыunclassified
“…Similarly, a post mortem study assessing causes of death histologically and with mycobaterial and bacterial cultures showed that TB contributed to death in 17 of 25 adults receiving ART at the time of death (65). Extremely drug-resistant TB carries a very poor prognosis, particularly in HIV-infected adults, 51% of whom were reported to have died within 30 days of its diagnosis (66), and in those who survived long enough to initiate XDR treatment, 55% died while receiving treatment (67).…”
Section: Tb Mortality and Its Preventionmentioning
confidence: 99%